Current treatment approaches for COVID-19 and the clinical value of transfusion-related technologies. (October 2020) - Li, Ying; Liu, Shanglong; Zhang, Shuchao; Ju, Qiang; Zhang, Shaoqiang; Yang, Yuanming; Wang, Haiyan
Abstract: COVID-19 is caused by SARS-CoV-2 which is a new enveloped virus that belongs to the Beta coronavirus genus. As a major health crisis, SARS-CoV-2 has infected over a million people around the world. There is currently no specific treatment available for patients with COVID-19 infection. Numerous potential therapies, including supportive intervention, immunomodulatory agents, antiviral therapy, and convalescent plasma transfusion, have been used in clinical practice. Herein, we summarize the current potential therapeutic approaches for diseases related to COVID-19 infection and discusses the clinical value of blood transfusion-related technologies used in COVID-19 treatment.